The presentation of moral community on Kap Serng Bang Fai - Phontip, Kittiphong; Meemana, Pikool; Yuenyaw, Sinsub (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2019)
This article is intended to present the concept of the presentation of moral community on Kap Serng Bang Fai. Kap Serng Bang Fai is an E-san poem. It has been improved as a folk media used for presenting a moral community of Ban Nongbua, Nongbua Sub-district, Atsamart District, Roi-Et Province. The content is related to a moral community which employs the concept of sufficiency economy, for instance, a use of manure. This leads to better harvest, environment and health of the population. Additionally, the people help each other, join festivals and regard temples as a spiritual center. According to data analysis, poetic compositions are classified into three patterns; Keang, Keangkoo and Teamekoo. In conclusion, to conserve this national wisdom, the folk media should be improved and promoted for informing advantageous information.